2013
DOI: 10.1016/j.jesp.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Scientific faith: Belief in science increases in the face of stress and existential anxiety

Abstract: Growing evidence indicates that religious belief helps individuals to cope with stress and anxiety. But is this effect specific to supernatural beliefs, or is it a more general function of belief — including belief in science? We developed a measure of belief in science and conducted two experiments in which we manipulated stress and existential anxiety. In Experiment 1, we assessed rowers about to compete (high-stress condition) and rowers at a training session (low-stress condition). As predicted, rowers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
213
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(244 citation statements)
references
References 22 publications
9
213
0
8
Order By: Relevance
“…We also administered the 10-item Belief in Science Scale developed by Farias and colleagues [67]. Examples of items are: “Science tells us everything there is to know about what reality consists of", and "All the tasks human beings face are soluble by science" (1 = Strongly disagree , 6 = Strongly agree , α = .96).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also administered the 10-item Belief in Science Scale developed by Farias and colleagues [67]. Examples of items are: “Science tells us everything there is to know about what reality consists of", and "All the tasks human beings face are soluble by science" (1 = Strongly disagree , 6 = Strongly agree , α = .96).…”
Section: Methodsmentioning
confidence: 99%
“…First, we investigated the relation between the MRS and strength of belief in science [67], and paranormal and religious beliefs [68, 69]. Because the MRS was developed to measure the extent to which individuals moralize a reliance on rational (vs. irrational ) methods of forming and evaluating belief, we expected it to be positively related to belief in science, as well as to our own measure of importance of rationality (IRS), and to be negatively related to paranormal beliefs and religiosity.…”
Section: Study 5: Convergent and Discriminant Validity Of The Mrsmentioning
confidence: 99%
“…There is some research showing that in the absence of religious beliefs, secular beliefs such as Humanism, atheism, science, reason, and various political ideologies can replace religion as a source of comfort and meaning (Amodio, Jost, Master, & Yee, 2007;Farias, Newheiser, Kahane, & de Toledo, 2013;Proulx, 2009;see Inzlicht, Tullett, & Good, 2011 for discussion). The other studies demonstrated that also mystical, esoteric, paranormal or superstitious beliefs might serve in part as a psychological coping mechanism that minimizes stress normally associated with psychological trauma (e.g., Irwin, 1994;Lange & Houran, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Given the opportunity, most people try to practice their personal ethics through prosocial behaviors. Since belief systems offer different frameworks to understand the purpose and meaning of life (Farias et al 2013;Hicks and King 2008;Willard and Norenzayan 2013), and since humans are generally concerned about morality regardless of their beliefs on afterlife (Jong et al 2012), belief systems shape the personal values that one holds dear. Thus, belief systems define the purpose and frame perceptions surrounding negotiations.…”
Section: Rationale and Assumptions: The Connection Between Interpersomentioning
confidence: 99%
“…One's belief system shapes her or his perspective of reality (Farias et al 2013;Hicks and King 2008). Individuals have subjective outlooks that frame subjective realities.…”
Section: Rationale and Assumptions: The Connection Between Interpersomentioning
confidence: 99%